Multiple Correlation Analysis of the Number of E-Commerce Entrepreneurs, Digital Literacy, and GDP per Capita on E-Commerce Transaction Value in Indonesia in 2020–2023 - Loranty Folia Simanjuntak; Shintami Oktavia; Anggi Pratiwi Sitorus; Muhammad Alhasymi Matondang (Outline Journal of Economic Studies, 2025)
This study aims to evaluate the relationship between the number of e-commerce entrepreneurs, digital literacy level, and GDP per capita on the e-commerce transaction value in Indonesia from 2020 to 2023. The approach used in this research is multiple correlation analysis, using secondary data obtained from BPS, the Ministry of Communication and Information Technology, and the Indonesian E-Commerce Association (idEA). The findings of this study indicate that all three independent variables have a very strong relationship with the e-commerce transaction value, evidenced by an R² value of 1.000 which shows that 100% of the variance in transaction value can be explained by the combination of these three variables. In separate analysis, GDP per capita has the most significant impact (97.5%), followed by digital literacy (93.1%), and the number of e-commerce entrepreneurs (80.9%). This result indicates that the development of the digital economy in Indonesia is greatly influenced by the purchasing power of the community, understanding of digital technology, and the presence of online business actors.